New insights into the effects of ethylene on ABA catabolism, sweetening and dormancy in stored potato tubers - Alamar, M. Carmen; Thompson, Andrew J.; Tosetti, Roberta; Chope, Gemma A.; Cools, Katherine; Waters, Amanda; McWilliam, S.; Terry, Leon A. (Cranfield University, 2020)
Underlying data for this paper includes: respiration rate, sprout assessment, sprout incidence, and abscisic acid (ABA) and ABA-metabolites concentration for potato tubers during postharvest storage.
Keywords: Abscisic acid'; 'ethylene'; 'cold-induced sweetening'; 'respiration rate'; 'Solanum tuberosum'; 'sprouting'; 'Kunitz-type invertase inhibitor'; 'ACO'; 'ACS'; '1-MCP'; 'Plant Physiology'; 'Plant Biology'; 'Plant Cell and Molecular Biology'